Characterization and molecular detection of pathogenicity and antibiotic resistance genes in Vibrio parahaemolyticus isolated from Pacific white shrimp - Muhammad Arif Mulya; Fachriyan Hasmi Pasaribu; Usamah Afiff; Munti Yuhana (Jurnal Akuakultur Indonesia)
ABSTRACT